2015
DOI: 10.1371/journal.pone.0127776
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of DREAM Promotes the Degeneration of Retinal Neurons

Abstract: The intrinsic mechanisms that promote the degeneration of retinal ganglion cells (RGCs) following the activation of N-Methyl-D-aspartic acid-type glutamate receptors (NMDARs) are unclear. In this study, we have investigated the role of downstream regulatory element antagonist modulator (DREAM) in NMDA-mediated degeneration of the retina. NMDA, phosphate-buffered saline (PBS), and MK801 were injected into the vitreous humor of C57BL/6 mice. At 12, 24, and 48 hours after injection, expression of DREAM in the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown that, in addition to RGCs, other retinal neurons are also impacted by NMDA-induced neurotoxicity (Chintala et al, 2015; Kuehn et al, 2017). In our present study, utilizing samples at 5 days post-injury, we investigated whether treatment with MDL improved the survival of neurons in the INL in response to NMDA treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that, in addition to RGCs, other retinal neurons are also impacted by NMDA-induced neurotoxicity (Chintala et al, 2015; Kuehn et al, 2017). In our present study, utilizing samples at 5 days post-injury, we investigated whether treatment with MDL improved the survival of neurons in the INL in response to NMDA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The NMDA receptor (NMDAR) subtypes play a major role in this process, mainly by increasing intracellular calcium (Ca 2+ ). Activation of NMDAR has been shown to promote neuronal death in the retina (Shen et al, 2006; Chintala et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At low concentrations (<50 nM) NMDA has been shown to damage amacrine cells but bipolar cell damage has only been reported for higher concentrations (>200 nM). 78 At 20 mM NMDA concentrations, substantial bipolar and interneuron cell damage will have occurred. We observed a significant protective effect of Lip A compared to the empty liposome Lip C ( P value < 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…In neuronal cells, DREAM acts as a transcriptional repressor involved in protein folding (28), presenilin-induced β-amyloid formation (13), nitric oxide-induced inflammatory pain (29), apoptosis (3033), and synaptic plasticity (34). Earlier work demonstrated that DREAM represses transcription of the PDYN (prodynorphin) gene in neuroblastoma cells (17).…”
Section: Function Of Dreammentioning
confidence: 99%
“…Studies using an inducible expression system in neuroglioma cells suggested that DREAM enhances apoptosis by altering the cytosolic Ca 2+ level and increasing caspase and calpain activities (31). Nonetheless, the role of DREAM in apoptosis may be cell specific since knockdown of DREAM attenuates apoptosis induced by increased cytosolic Ca 2+ levels in HeLa cells and a T-lymphocyte cell line (32), whereas down-regulation of DREAM in retinal ganglion cells promotes apoptosis (33). …”
Section: Function Of Dreammentioning
confidence: 99%